Antidiabetic potential of the leaf extract of Centella asiatica in alloxaninduced diabetic rats - Emran, Talha Bin; Dutta, Mycal; Uddin, Mir Muhammad Nasir; Nath, Aninda Kumar; Uddin, Md Zia (Jahangirnagar University Journal of Biological Sciences, 2016)
The study was designed to evaluate the glucose and cholesterol lowering effect of the aqueous extract of Centella asiatica leaf using the alloxan-induced diabetic rats and compared the activity with diabetic control and antidiabetic drug (Glibenclamide). Leaf extract (50 mg/kg) of C. asiatica and Glibenclamide were administered to normal and experimental diabetic rats for the duration of 10 days. In the alloxan-induced diabetic rat model, C. asiatica extract (50 mg/kg) significantly (p < 0.05) lowered the fasting blood glucose level as well as the total cholesterol level. Serum insulin levels were not stimulated in the animals treated with the extract. In addition, changes in body weight, serum lipid profiles and liver glycogen levels assessed in the extract treated diabetic rats were compared with diabetic control and normal animals. Significant results (p < 0.05) were observed in the estimated parameters. Surprisingly, body weight was increased significantly (p < 0.05) in the C. asiatica treated diabetic group. Phytochemical screening showed the presence of alkaloids, flavonoids, glycosides, steroids and tannins in significant amounts Jahangirnagar University J. Biol. Sci. 4(1): 51-59, 2015 (June)